1993
DOI: 10.1042/bj2910071
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C-terminal domain of pulmonary surfactant protein A in binding to alveolar type II cells and regulation of phospholipid secretion

Abstract: Surfactant protein A (SP-A), with a reduced denatured molecular mass of 26-38 kDa, is characterized by a collagen-like sequence in the N-terminal half of the protein. This protein forms an oligomeric structure which is dependent upon this collagenous domain. SP-A has been demonstrated to function as an inhibitor of phospholipid secretion by primary cultures of alveolar type II cells via a cell surface receptor for the protein. However, the receptor-binding domain of SP-A has not been identified. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
(7 reference statements)
2
26
0
Order By: Relevance
“…The capacity of SP-A to function as the modulator of surfactant secretion and turnover appears to involve the binding of SP-A to type II cells, probably via specific cell surface receptors (Murata et al, 1993;Wright et al,, 1989;Kuroki et al, 1988). Previously we have reported that secretagogues enhanced the uptake of lipid and protein components of lung surfactant by isolated perfused lungs (Fisher et al, 1991) and by type II cells (Chinoy et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of SP-A to function as the modulator of surfactant secretion and turnover appears to involve the binding of SP-A to type II cells, probably via specific cell surface receptors (Murata et al, 1993;Wright et al,, 1989;Kuroki et al, 1988). Previously we have reported that secretagogues enhanced the uptake of lipid and protein components of lung surfactant by isolated perfused lungs (Fisher et al, 1991) and by type II cells (Chinoy et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SP-A may play a pivotal role in the regulation of surfactant turnover. Type II cells express a high affinity receptor for SP-A (Kuroki et al, 1988, Wright et al, 1989) that recognizes the carboxyl-terminal portion of the SP-A molecule (Wright et al, 1989;Murata et al, 1993). Using an anti-idiotypic antibody approach, two groups have identified type II cell membrane proteins specific for SP-A with molecular masses of either 30-kDa (Strayer et al, 1993) or 55 kDa (Stevens et al, 1995).…”
mentioning
confidence: 99%
“…SP-A also interacts with alveolar type II cells (10,11). Previous studies have identified the CRDs as essential for the interactions of lung collectins with lipids and type II cells (31)(32)(33). In this study, we focused on the CRD regions of SP-A and SP-D, and progressively longer carboxyl-terminal regions of the SP-D CRD were substituted for the corresponding SP-A CRD regions.…”
Section: Characterization Of Chimeric Recombinant Proteins-wildmentioning
confidence: 99%
“…Although lung collectins possess homologous structures and exhibit similar carbohydrate binding specificities, they show quite different properties of binding lipids and interacting with alveolar type II cells. Previous studies have suggested that the CRD of SP-A or SP-D plays a critical role in interactions with lipids and type II cells (31)(32)(33)(34). However, the regions of the CRDs that are essential for lipid binding and type II cell interactions have not yet been fully identified.…”
mentioning
confidence: 99%
“…Receptor binding is required for inhibition of surfactant secretion and enhancement of phospholipid uptake activities by SP-A (18,19,32 (Fig. 2).…”
Section: Expression and Characterization Of Position 197 Mutants-in Amentioning
confidence: 99%